2016
DOI: 10.1021/acs.inorgchem.6b00221
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Synthesis of Two Porphyrin-Based MOFs with Gallium and Indium

Abstract: Two porphyrin-based metal-organic frameworks (MOFs) containing gallium or indium, [Ga2(OH)2(H2TCPP)]·3DMF·3H2O (Ga-PMOF) and [In2(OH)2(H2TCPP)]·3DMF·4H2O (In-PMOF) (H6TCPP = 4-tetracarboxyphenylporphyrin), were discovered using high-throughput methods. The structure was refined by the Rietveld-method starting from the structure model of Al-PMOF, [Al2(OH)2(H2TCPP)]. The new PMOFs exhibit BET surface areas between 1150 and 1400 m(2) g(-1) and are also porous toward CO2 (Ga-PMOF, 15.2 wt %; In-PMOF, 12.9 wt %). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 52 publications
5
33
0
Order By: Relevance
“…The PXRD patterns of three obtained samples matched with the simulated patterns, respectively in Figure S1-3. N2 isotherms collected at 77 K revealed that Al-PMOF, Ga-PMOF, and In-PMOF have estimated Brunauer-Emmett-Teller (BET) surface areas of 2060, 1600, and 1610 m 2 g -1 , respectively, which are comparable to the reported values [28][29] in Figure S4a. Density functional theory (DFT) pore size distributions of all samples appeared at around 1 nm, which corresponds to the channel along with one-dimensional metal nodes, as shown in Figure S4b.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…The PXRD patterns of three obtained samples matched with the simulated patterns, respectively in Figure S1-3. N2 isotherms collected at 77 K revealed that Al-PMOF, Ga-PMOF, and In-PMOF have estimated Brunauer-Emmett-Teller (BET) surface areas of 2060, 1600, and 1610 m 2 g -1 , respectively, which are comparable to the reported values [28][29] in Figure S4a. Density functional theory (DFT) pore size distributions of all samples appeared at around 1 nm, which corresponds to the channel along with one-dimensional metal nodes, as shown in Figure S4b.…”
supporting
confidence: 77%
“…Recently, porphyrin-based MOFs with one-dimensional metal (Al, Ga, and In) nodes and bridging -OH sites have been studied. [27][28][29][30] The meso-tetra(4-carboxyl-phenyl) porphyrin (TCPP) based MOFs, M2(OH)2(TCPP) (M = Al, Ga and In), referred to as Al-PMOF, Ga-PMOF, and In-PMOF, possess infinite rod-packing chains ([M(OH)(─COO)2]∞) linked by a free-base porphyrin linker, giving rise to one-dimensional channels of approximately 1 nm ( Figure 1). Herein, we report the syntheses of three Al-, Ga-, In-PMOFs and the evaluation of NH3 adsorption properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These types of reaction vessels were selected as they are commercially available, low priced and are already frequently used in laboratory practice. 25,26 In the case of an in situ analysis of a chemical reaction, it is advisable to investigate the reaction system thoroughly prior to the beamtime using ex situ methods to develop an understanding of the reaction progress and the influence of different parameters on the product formation. For some reactions, however even minor parameter changes like a different composition of the reaction vessel (glass or PTFE, Polytetrafluorethylen) or a variation in the surface-to-volume ratio can already influence the outcome of the experiment.…”
Section: B Design Of the In Situ Cellmentioning
confidence: 99%
“…While a greater number of coordination polymers (CPs) and metal‐organic frameworks (MOFs) containing transition metals and lanthanides are known, a limited number of group 13 metal based coordination polymers are reported. For instance, the largest range of known CPs and MOFs are carboxylate‐based, whereas, CPs based on N‐donor ligands account for only a small share . In complexes containing group 13 metal halides, different coordination numbers (CN = 4, 5, 6) of the central atom can be found, depending on the complex composition, the type of the metal halide and the Lewis basicity of the used ligand .…”
Section: Introductionmentioning
confidence: 99%